JB Pritzker, Jennifer Pritzker, & Synthetic Sex Identities (Tablet Magazine, 2022)
JB Pritzker and Jennifer Pritzker are advocates for expanding public consciousness of Synthetic Sex Identities and the gender spectrum.
Section: News
Keywords: pritzker; trans